Perancangan Motel Bergaya Desain Post-Modern di Surabaya - Evelyn Nuryadi; Stephanus Pantja Honggowidjaja (Intra, 2019)
Accommodation is one of the important things in tourism. Nowadays, especially in Surabaya, there are rarely motels with high quality facilities. Although the motel has a cheaper price than hotels, visitors still need to feel comfortable when staying at the motel. This inspired the author to design a Post-Modern style motel in Surabaya. The design of this motel is intended for people who are in transit or backpackers so they  can get a good price accommodation with comfortable and pleasant experience. Post-Modern itself is a dualism flow that combines modern functional architecture with decorative ornaments in the past. This Post-Modern design style inspired author to design a simple Motel, with a touch of decoration that makes a motel not only a place to stay, but becomes something unique and interesting for tourist and the people of Surabaya itself.